Multiparametric analysis of preoperative lymphatic mapping with the use of combined deep plus superficial radiotracer injection technique in early breast cancer - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2008)
Objectives According to literature, combined tracer injection techniques seem to be the more powerful choice to eliminate technical and patient-related limitations. In this study, we analysed the quantitative performance parameters of combined deep plus superficial radiotracer injection and their correlation with a set of clinical, pathological and technical factors. Methods One hundred and sixteen women who underwent preoperative sentinel lymph node (SLN) mapping were studied prospectively. All patients received the simultaneous deep and superficial injection of Tc-99m-nanocolloid. Mapping success rate, mean number of SLNs per patient and radiotracer uptake of SLNs were determined. The possible effects of age, tumour stage, laterality and location, type and time of previous biopsy, and SLN status on the quantitative parameters were analysed. Results Axillary SLNs were visualized in all cases. Mean number of axillary SLNs was 2.15 and advanced age (>50) significantly decreased the number of SLNs. Radiotracer uptake of SLNs was also significantly decreased by advanced age and a shorter time interval between biopsy and mapping (<10 days). Extra-axillary SLN visualization rates for medial, lateral and periareolar injection sites were 32%, 16% and 8%. Although SLN gamma probe counts were significantly higher in the single-day protocol, the 2-day protocol gave better contrast values which was also an important parameter in lesion detection. Conclusion The combined radiotracer injection technique successfully demonstrated axillary and extra-axillary SLNs. Advanced age and previous biopsy time can lower the accuracy and reliability of SLN biopsy. Although periareolar injection gave the best results for the axilla, it was still insensitive for extra-axillary SLNs in spite of deep injection.
Keywords: combined injection technique; deep injection; preoperative lymphoscintigraphy; sentinel lymph node; superficial injection; SENTINEL NODE BIOPSY; INTERNAL MAMMARY CHAIN; CLINICAL-IMPLICATIONS; LYMPHOSCINTIGRAPHY; VISUALIZATION; LOCALIZATION; DRAINAGE; FAILURE; AXILLA; PROBE